Translating the heterogeneous literary writing of Taiwan "Musha Incident": an interview with Michael Berry. Issue 3 (2nd September 2019) - Yang, Xiaohua; Berry, Michael
ABSTRACT: This interview with Michael Berry was conducted on June 14 and 15, 2016 at the University of California, Santa Barbara upon the forthcoming of the English translation of Yusheng ( 《餘生》 ) from Columbia University Press. The dialogue between Xiaohua and Michael Berry provides the reader with fascinating observations and comments about the tribulations and rewards of moving texts like Yusheng and The Song of Everlasting Sorrow: A Novel of Shanghai ( 《長恨歌》 ) from a source language to the target language. Berry illuminates the translational process of carrying Wu He's (舞鶴) heterogeneous literary writing of Taiwan "Musha Incident" (霧社事件) across the bridge into the English-speaking world. Berry speaks about the commitment of the translator to both the author and the target audience. the ethics of difference and ethics of innovation in preserving the historical, cultural and linguistic values of the source language in the translation into the target language. Wu He's Remains of Life, after its publication in April 2017, has received great critical acclaims and was shortlisted for the Best Translated Books Award (BTBA) in 2018.